2009
DOI: 10.1007/s12011-009-8479-6
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Cadmium Co-exposure Mediated Toxic Insults on Hepatic Steroid Metabolism and Antioxidant System of Adult Male Rats

Abstract: The redox status and steroid metabolism of liver of adult male rat exposed to lead (Pb) and cadmium (Cd) either alone or in co-exposure (0.025 mg/kg body weight intraperitoneally/15 days) was studied. Pb and Cd significantly accumulated in the liver. The activity of steroid metabolizing enzymes 17-betahydroxysteroid oxidoreductase and uridine diphosphate-glucuronyltransferase were decreased in experimental animals. 17-beta-Hydroxysteroid dehydrogenase was reduced to 33%, 38%, and 24% on treatment of Pb, Cd, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
1
9
1
1
Order By: Relevance
“…Pandya et al (2010) also obtained similar results in liver of male rats co-exposed to Pb and Cd. Some metals like Al tend to be more concentrated in the lung as age increases (Schaller et al 1994b) and others, like Be tend to enter via respiratory tract (Rossman 1994).…”
Section: Discussionsupporting
confidence: 69%
“…Pandya et al (2010) also obtained similar results in liver of male rats co-exposed to Pb and Cd. Some metals like Al tend to be more concentrated in the lung as age increases (Schaller et al 1994b) and others, like Be tend to enter via respiratory tract (Rossman 1994).…”
Section: Discussionsupporting
confidence: 69%
“…Both in vivo and in vitro studies have suggested generation of reactive oxygen species (ROS) and alteration of antioxidant system in animals as one of the mechanisms for the toxic effects of lead and cadmium [47][48][49][50][51]. Our results show that ovarian GSH content is decreased in all the metal-treated groups.…”
Section: Discussionmentioning
confidence: 52%
“…Experimental and epidemiological evidence indicates that combination effects generated by multi-heavy metals might be quite different from that induced by the same individual metal, because heavy metals at individual low acting concentrations can elicit higher toxicity on interactions with other environmental toxicants [ 11 , 12 , 13 , 14 ]. Goyer [ 15 ] has shown toxic metals have significant interactions with essential metals (iron, manganese, calcium) which can influence the essential metal status in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Pandya et al . [ 14 ] showed that under similar dosages, when Pb and Cd are present together, the toxic effect is antagonized by co-exposure due to possible competition among Pb and Cd for hepatic accumulation. Damian et al .…”
Section: Introductionmentioning
confidence: 99%